Proposta de intervenção para a melhoria da coleta seletiva no IFSudeste MG – Câmpus Barbacena - Campos, Ana Carolina Moraes (2018)
The universities and educational institutions of the federal technical network are communities that significantly impact the environment in which they are inserted. Due to the nature of their activities, they generate significant quantities of effluents, solid wastes and atmospheric emissions of diverse chemical compositions, when not properly managed result in different negative impacts like environmental, as well as economic and social. The study’s objective was to evaluate the educational intervention influence on the Solidary Selective Collection Program (PCSS) efficiency in the Barbacena campus of the Federal Institute of Education, Science and Technology of the Southeast of Minas Gerais (IFSUDESTE MG). The following educational intervention stages were carried out: applications of questionnaires to evaluate environmental perception, classroom incursion and meeting with the servers responsible for cleaning the campus. In order to evaluate the influence of these stages in the waste disposal, gravimetric compositions of the discarded residues were carried out in the external collectors available in the institution. In addition, it was studied the substitution of the external collectors set with five compartments (paper, plastic, metal / glass, organic matter and non-recyclable) for the two-compartment set (recyclable and non-recyclable) in ten sites that shows the lowest rates segregation and disposal. For this, the difference between the percentage of correctly discarded waste and potentially recyclable waste was evaluated, before and after the proposed interventions. The data obtained were analyzed by statistical measures of central tendency and dispersion, and tested using appropriate statistical tests. After the educational interventions in the classroom and with the employees of the cleaning service, the percentage of correctly discarded waste increased from 46.50% to 66.13% (r = 0.44), as well as the percentage of potentially recyclable waste (from 40.04% to 52.21%, r = 0.12). The questionnaires result shows that there is an environmental perception on the academic community part, once of 25 questions analyzed, 15 presented a statistically significant difference in the number of correct answers. A proposed two-compartment external collector (recyclable and non-recyclable) presented better than the five compartments, once it is a 29.72% increase in waste correctly disposed. On the other hand, there was no increase in the recyclable waste potential, with a 9.89% decrease on average. Therefore, it was possible to conclude that the educational intervention proposed in the present study had a direct impact on the recyclable waste discarding and on environmental perception by the academic community of IFSUDESTE-MG. Thus, it emphasizes the importance of PCSS be associated with environmental education programs, with a continuous focus on activities that stimulate the participation of the entire academic community.